BRAND IMAGE, KUALITAS PRODUK, MINAT BELI DAN KEPUTUSAN PEMBELIAN - Meyzi Heriyanto, Ogi Rifansyah, Okta Karneli, (Jurnal Ilmu Administrasi Negara, 2019)
Brand Image, Product Quality, Purchase Interests and Purchasing Decisions. The purpose of this study is to determine the brand image, product quality, buying interest and purchasing decisions. The number of respondents as many as 90 people were randomly drawn from the population. Data collection techniques are questionnaires from the results of data analysis which include outer models, convergent validity, discriminant validity, composite reliability, average variance extracted, and inner models show that brand image and product quality have an influence on buying interest and purchasing decisions for MPV types of Suzuki brands. Ertiga at PT. Sejahtera Buana Trada Pekanbaru with a value of 0.75 means that the i nfluence of brand image variables and product quality on buying interest and purchasing decisions is 75%. The results of hypothesis testing found that the f-count is greater than the f-table which means that Ha is accepted.